1452. Non-invasive Pneumococcal Pneumonia in Adults in Portugal: Continued Decline of PCV13 Serotypes (2015–2017). (26th November 2018) - Silva-Costa, Catarina; Lopes, Elísia; Ramirez, Mario; Melo-Cristino, Jose; ,
Abstract: Background: In 2015, PCV13 was introduced in the National Immunization Plan in Portugal for children, although it was not significantly used in adults. However, changes in the pneumococcal population causing non-invasive pneumococcal pneumonia (NIPP) in adults (≥18 years) can occur due to herd effects. To evaluate this, we monitored the serotypes and antimicrobial resistance of adult NIPP isolates in 2015–2017. Methods. A total of 1, 142 isolates were recovered, serotyped by Quellung and tested for susceptibility to antimicrobials by disk diffusion or Etest. Results: Among the 1, 142 isolates, 52 different serotypes were found and 59 isolates were nontypeable (5%). The most common were serotypes 3 (13%), 11A (8%), 19F, 9N and 23A (5% each), 23B, 16F and 6C (4% each). There were strong variations in the proportion of some serotypes, suggesting that factors other than vaccine pressure could also impact on serotype prevalence. Although a considerable number of isolates still expressed the additional serotypes included in PCV13 (addPCV13 = 200), the overall proportion of addPCV13 serotypes remained relatively stable in this time period. However, when comparing with the previous period (2012–2014), there was a significant decrease in the proportion of addPCV13 serotypes, from 22 to 17.7% ( P = 0.007). Serotypes included in PCV7 (11%, n = 122) and the serotypes exclusively found in the 23-valent polysaccharide vaccine (30%, n = 339) did not change significantly in 2015–2017. Non-vaccine types were expressed by 42% of the isolates ( n = 481) and their proportion was also stable throughout the study. Overall, resistance did not change relative to 2012–2014, with 22% erythromycin resistance and 18% penicillin nonsusceptibility. Conclusion: After the introduction of PCV13 in the National Immunization Plan for children, a significant decrease in the proportion of PCV13 serotypes was noted in the adult population, although a considerable fraction of disease is still caused by vaccine serotypes. Moreover, nonvaccine serotypes are becoming important causes of NIPP, emphasizing the importance of continued surveillance studies. Disclosures: M. Ramirez, Pfizer: Speaker's Bureau, Speaker honorarium; GlaxoSmithKline: Consultant, Consulting fee; Merck Sharp and Dohme: Consultant, Consulting fee. J. Melo-Cristino, Pfizer: Grant Investigator and Speaker's Bureau, Research grant and Speaker honorarium; Merck Sharp and Dohme.: Speaker's Bureau, Speaker honorarium.